Does financial inclusiveness affect economic growth? new evidence using a dynamic panel threshold regression - Abdul Karim, Zulkefly; Nizam, Rosmah; Law, Siong Hook; Hassan, M. Kabir (Elsevier, 2021)
This study examines the impact of financial inclusiveness on economic growth using a sample of 60 countries from 2010 to 2017. A new Index of Financial Inclusion (IFI) has been constructed for each country to determine their level of financial inclusiveness across time. The main findings using a dynamic panel threshold estimation technique revealed a threshold effect in the financial inclusiveness-growth nexus. We find that the level of financial inclusiveness is beneficial and positively affects economic growth at lower or upper threshold levels in a different regime. Furthermore, the threshold impact of financial inclusion is positive and has a more significant growth-enhancing effect among less developed and emerging market countries relative to developed ones. Thus, policymakers in less developed and emerging market countries need to prioritize their efforts to raise the level of financial inclusiveness in place of its greater growth-enhancing effect in these countries.